The influence of Sm2O3 dopant on structure, morphology and transport critical current density of MgB2 wires investigated by using the transmission electron microscope - Daniel Gajda; Michał Babij; Andrzej Zaleski; Doğan Avci; Fırat Karaboga; Hakan Yetis; Ibrahim Belenli; Dariusz Zasada; Damian Szymański; Małgorzata Małecka; Wojciech Gil; Tomasz Czujko (Journal of Magnesium and Alloys)
This study reports results for the morphology, crystal structure and critical parameters of Sm2O3-doped MgB2 wires with low and high initial filling densities. The transmission electron microscope (TEM) images were done for the longitudinal section of MgB2 wires. The results show that the Sm2O3 admixture significantly changes the morphology of the MgB2 material, accelerates the formation of the MgB2 phase, does not form rectangular MgB2 crystallites, does not leave pure Mg, and forms Sm2O3 areas of 10 nm and 20 nm. The effects of Sm2O3 addition on MgB2 formation in superconducting wires were revealed in detail in this study. Additionally, Sm2O3 causes the formation of point pinning regions that significantly increase the critical transport current density at the temperature range from 15 K to 30 K. The TEM images point out that rectangular MgB2 crystallites are formed in undoped MgB2 wires, which have not been previously reported. XRPD results showed that short-term heating allowed obtaining a larger amount of MgB2 phase for the MgB2 wire with high initial filling density. On the other hand, long heating time and high initial density slow down the creation of MgB2 phase when the Mg is in the solid state.